Control of technical and tactical readiness of athletes in all-style karate - Akopyan A.V. ,; Shakhov A.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to improvement of athletes control over the technical and tactical readiness of athletes in all-style karate. Methods and structure of the study. 14 representatives of the Russian national all-style karate team took part in the pedagogical experiment, which took place during the All-Russian training camp, in preparation for the World Championship, analysis of information sources, control tests, expert assessment, mathematical and statistical methods. Results and conclusions. The experiment made it possible to determine the current state of the theory and practice of monitoring the technical and tactical readiness of athletes in all-style karate. A promising direction of this work is the use of artificial intelligence, implemented in relevant digital resources.